Caffeic Acid, an Allelochemical in Artemisia argyi, Inhibits Weed Growth via Suppression of Mitogen-Activated Protein Kinase Signaling Pathway and the Biosynthesis of Gibberellin and Phytoalexin - Chen, Le; Li, Jinxin; Zhu, Yunyun; Guo, Lujuan; Ji, Rongsheng; Miao, Yuhuan; Guo, Lanping; Du, Hongzhi; Liu, Dahui (Frontiers in Plant Science, 2022)
Artemisia argyi is widely distributed in Asia, and it often becomes the dominant population in the field because of its strong ecological niche competitiveness. Allelochemicals secreted by plants are generally considered an important reason for their dominance in ecological competition. In this study, the allelochemicals in A. argyi were screened by a series of experiments and their mechanisms were explored via transcriptomics. First, the inhibitory effects of A. argyi on Echinochloa crusgalli, Setaria viridis, Portulaca oleracea and Amaranthus retroflexus were evaluated. Then, we carried out a qualitative and quantitative analysis of the chemical composition of the aqueous extract of A. argyi to screen for potential allelochemicals that can inhibit weed growth. Four potential allelochemicals were quantified: neochlorogenic acid (5-CQA), chlorogenic acid (3-CQA), cryptochlorogenic acid (4-CQA), and caffeic acid (CA). Coincidentally, their allelopathic effects on weeds seemed to be identical to their content, in the order CA > 4-CQA > 5-CQA > 3-CQA. These findings suggested that CA might be the main allelopathic compound in the aqueous extract of A. argyi. Subsequently, the allelopathic effect and molecular mechanism of CA on S. viridis leaves were investigated. The physiological results showed that CA significantly induced reactive oxygen species (ROS) production, led to malondialdehyde (MDA) accumulation, and disrupted enzyme activities (POD, SOD, CAT) in S. viridis leaves. Moreover, transcriptome results revealed that CA inhibited S. viridis growth by downregulating multiple genes involved in gibberellin (GA) and phytoalexin biosynthesis and MAPK signalling pathways. In addition, differentially expressed genes (DEGs) related to the biosynthesis and signalling pathways of phytohormones were verified by RT-qPCR. Taken together, this study may be the first to identify allelochemicals and explore their molecular mechanism about A. argyi. Importantly, the ecological advantages of A. argyi could be applied to ecological regulation and the development of botanical herbicides.